2021
DOI: 10.1093/nutrit/nuab006
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics supplementation in patients with colorectal cancer: a systematic review of randomized controlled trials

Abstract: Context Colorectal cancer (CRC) is a leading cause of cancer deaths. Recently, much attention has been given to the microbiome and probiotics as preventive and therapeutic approaches to CRC and the mechanisms involved. Objectives To interpret the findings of randomized controlled trials (RCTs) of probiotics relative to patients with CRC and to outline challenges of and future directions for using probiotics in the management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 65 publications
1
23
2
1
Order By: Relevance
“…Lately, the interest in studying how microbiome modulation can be utilized in the prevention and management of colorectal cancer has increased significantly. Several reviews assessed the impact of gut microbiota and probiotic supplementation in CRC patients [72][73][74]. However, most of these reviews focused on specific evaluations or subgroups of patients, such as being limited to fecal samples or post-op patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the interest in studying how microbiome modulation can be utilized in the prevention and management of colorectal cancer has increased significantly. Several reviews assessed the impact of gut microbiota and probiotic supplementation in CRC patients [72][73][74]. However, most of these reviews focused on specific evaluations or subgroups of patients, such as being limited to fecal samples or post-op patients.…”
Section: Discussionmentioning
confidence: 99%
“…ESMO, MASCC, and ESPEN guidelines already consider that certain probiotic strains may be used to prevent chemotherapy/radiotherapy treatment-related diarrhoea [5][6][7][8]. In a recent systematic review, the use of probiotics during colorectal cancer treatment was deemed safe; however, the authors did not include any CIT clinical trials [9]. In contrast, other studies have found that probiotics might decrease the response to CIT, and there is a lack of evidence comparing each individual approach/strategy, e.g., probiotics vs. fibre, with regards to improved treatment response [10].…”
Section: Review Discussion and Key Studiesmentioning
confidence: 99%
“…Intake of probiotics which are beneficial microorganisms during chemotherapy has been proven to help to lessen the negative effects of chemotherapeutic agents on the gut microbiota 100 . Although probiotic formulations specific for cancer patients are not yet popular, several studies have shown that administering probiotics either as a mixture or singly to cancer patients is beneficial for the management of microbiota‐mediated drug activity modulation 101,102 …”
Section: Influence Of Gut Microbiota On Chemotherapeutic Drugsmentioning
confidence: 99%